Peran Media Massa Dalam Menyerukan Budaya Keberagaman di Indonesia - pradika w, swandaru; Aris Saefulloh; Famuji, Untung (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Indonesia’s cultural diversity serves as a defining characteristic of its national identity, yet this pluralism frequently generates intercultural conflicts manifesting through ethnic, religious, and racial tensions across multiple regions. This study investigates mass media's strategic role in promoting diversity culture within Indonesia's pluralistic society. Employing a qualitative descriptive methodology with literature review approach, this research analyzes how mass media functions as a critical bridge for cross-cultural communication through its extensive audience reach and cultural framing capabilities. Findings reveal that mass media possesses significant potential to foster mutual understanding and acceptance among diverse cultural groups by serving as an informational conduit that connects disparate cultures. However, commercial imperatives often compromise this function, leading to stereotype reinforcement rather than cultural appreciation. The study concludes that while mass media holds transformative power in cultivating diversity awareness, realizing this potential requires institutional commitment to journalistic independence, editorial neutrality, and prioritization of social responsibility over profit maximization. Recommendations include strengthening media literacy programs and developing alternative media platforms that genuinely serve public interest.